Abusive supervision and employee engagement and satisfaction: the mediating role of employee silence. Issue 9 (12th March 2020) - Wang, Chih-Chieh; Hsieh, Hui-Hsien; Wang, Yau-De
Abstract : Purpose: Previous studies have found that abusive supervision undermines employees' work motivation and attitudes, namely work engagement and job satisfaction. However, less is known about the mechanisms by which abusive supervision negatively relates to employees' work engagement and job satisfaction. Drawing on conservation of resources theory, this study examines employee silence as a mediating mechanism linking abusive supervision to employees' work engagement and job satisfaction. Design/methodology/approach: Survey data were collected from a sample of 233 full-time employees of a large hotel service company in Taiwan. Structural equation modeling analyses were conducted to test the hypotheses. Findings: The results showed that abusive supervision has a positive association with employee silence. Moreover, the results showed that employee silence mediates the negative associations of abusive supervision with employees' work engagement and job satisfaction. Practical implications: The results suggest that organizational managers should provide supervisors with leadership interventions to prevent the occurrence of abusive supervision. Furthermore, organizational managers should provide employees with opportunities to voice their concerns through the use of organizational communication and participation, which can reduce employee silence and subsequently foster employee engagement and satisfaction at work. Originality/value: This study advances our understanding of how abusive supervision results in poor work motivation and attitudes among employees. This contributes to the literature by identifying employee silence as a suitable mediating mechanism linking the negative associations of abusive supervision with employees' work engagement and job satisfaction.